2017
DOI: 10.1038/s41598-017-13994-w
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β signalling and PEG10 are mutually exclusive and inhibitory in chondrosarcoma cells

Abstract: Histological distinction between enchondroma and chondrosarcoma is difficult because of a lack of definitive biomarkers. Here, we found highly active transforming growth factor-β (TGF-β) and bone morphogenetic protein (BMP) signalling in human chondrosarcomas compared with enchondromas by immunohistochemistry of phosphorylated SMAD3 and SMAD1/5. In contrast, the chondrogenic master regulator SOX9 was dramatically down-regulated in grade 1 chondrosarcoma. Paternally expressed gene 10 (PEG10) was identified by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…2 a, PEG10 is relatively highly expressed in placenta, adrenal, ovary, testis and brain, but the expression levels are pretty low in other tissues, which are consistent with the previous literature [ 1 , 7 – 9 ]. As shown in Table 1 , several studies have reported PEG10 is positively expressed in a variety of cancers such as hepatocellular carcinoma (HCC) [ 9 , 16 19 ], pancreatic carcinoma [ 20 ], breast cancer [ 10 ], prostate cancer [ 10 ], gallbladder carcinoma [ 21 ], thyroid cancer [ 22 ], oral squamous cell carcinoma [ 23 ], colon cancer [ 24 ], enchondromas [ 25 ] and B-cell chronic lymphocytic leukemia (B-CLL) [ 26 ]. Worth noting was that the amplification of PEG10 gene copy numbers detected in HCC also contributed to PEG10 overexpression [ 17 , 27 29 ].…”
Section: The Expression Levels Of Peg10 In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…2 a, PEG10 is relatively highly expressed in placenta, adrenal, ovary, testis and brain, but the expression levels are pretty low in other tissues, which are consistent with the previous literature [ 1 , 7 – 9 ]. As shown in Table 1 , several studies have reported PEG10 is positively expressed in a variety of cancers such as hepatocellular carcinoma (HCC) [ 9 , 16 19 ], pancreatic carcinoma [ 20 ], breast cancer [ 10 ], prostate cancer [ 10 ], gallbladder carcinoma [ 21 ], thyroid cancer [ 22 ], oral squamous cell carcinoma [ 23 ], colon cancer [ 24 ], enchondromas [ 25 ] and B-cell chronic lymphocytic leukemia (B-CLL) [ 26 ]. Worth noting was that the amplification of PEG10 gene copy numbers detected in HCC also contributed to PEG10 overexpression [ 17 , 27 29 ].…”
Section: The Expression Levels Of Peg10 In Cancersmentioning
confidence: 99%
“…In HCC, PEG10 was increased after treating HepG2 cells with TGF-β1 [ 44 ]. However, the mutual inhibition effect of PEG10 and TGF-β signaling was found in chondrosarcoma and enchondroma [ 25 ]. Shinohara et al proposed that TGF-β might inhibit PEG10 expression through the downregulation of c-MYC [ 10 , 25 , 35 ].…”
Section: The Expression Levels Of Peg10 In Cancersmentioning
confidence: 99%
“… 41 In other report, SOX9 is dramatically decreased in grade 1 chondrosarcoma. 42 Taken these, SOX9 expression level may not be used as a prognostic marker, but can be used as a therapeutic target.…”
Section: Sox4 and Sox9mentioning
confidence: 99%
“… 43 44 BMPRs and runt-related transcription factor 2 (RUNX2) signalling in bone development and carcinogenesis are well known but not in chondrogenesis. Shinohara et al 42 have revealed that phosphorylated Smad3 and Smad1/5 is increased in chondrosarcoma, and Yang et al 45 have shown that BMPR2 and RUNX2 expression is correlated with poor prognosis in 57 patients with various grades chondrosarcoma. 45 BMPR2 downstream Smad1/5 signal promotes tumour growth of chondrosarcoma cells in vivo.…”
Section: Transforming Growth Factor-beta and Bone Morphogenetic Protementioning
confidence: 99%
See 1 more Smart Citation